-Jag älskar att vara kvinna! Eller, vad är det för kvinnligt med Kvinnobiblioteket? - Strandberg, Åsa (Högskolan i Borås, Institutionen Biblioteks- och informationsvetenskap / Bibliotekshögskolan, 1995)
"What's feminine about the Women's library?" This library, Kvinnobiblioteket, is abranchoffice at Björkskatan in the city of Luleå, and the introducing question is thestartingpoint of this essay. To find some possible answers is its object.One way of describing what's feminine about Kvinnobiblioteket is through presenting itsobjective, ambitions and methods of working. That is done mostly in a chapter headlined"Kvinnobiblioteket", and shows how the women's perspective concerns for exarnplepurchase of books and magazines, displaying of books, the opening hours, design etc.Although the focus in the survey is not in the former kind of description, but in the interviewsbeing made during a two week long period of time with ten women at Kvinnobiblioteket(both library user and personnel) at spring 1995. The results of the interviewsthen have been compared with theories from psychological-, feminist-, literature- andlibrary and information sciences, as we11 as to former surveys and essays.The material together leads to some keywords that seem to be important when trying tofind out what's female about the women's library. They are, for example, such as:accepting, care, solidarity, sensitive ears and keenly awareness of the customers needs,commitment and willingness to cooperate. The meaning of the keywords are somewhatexpressed in the objective of the women's library, to stress female knowledge andexperience, to make them visible.